Solvability of a Elliptic-Parabolic (Hyperbolic) Type Chemotaxis System in a Bounded Domain (Journal of Partial Differential Equations, 2020)
In this paper, we use contraction mapping principle and operator-theoreticapproach to establish local solvability of the elliptic-parabolic (hyperbolic) Type Chemotaxis System. In addition, global solvability of the systems is considered by some uniform estimates.
Keywords: Elliptic-parabolic (hyperbolic) system; chemotaxis model; local existence; global existence.